2007
DOI: 10.1097/sla.0b013e31811ea962
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Margins on Outcome After Hepatic Resection for Colorectal Metastasis

Abstract: This study provides evidence that margin width of >1 cm is optimal and is an independent predictor of survival after hepatic resection for colorectal metastasis. However, subcentimeter resections are also associated with favorable outcome and should not preclude patients from undergoing resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
153
0
31

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(194 citation statements)
references
References 26 publications
10
153
0
31
Order By: Relevance
“…More wedge resections can be performed because several recent studies have indicated that a margin less than 1 cm is not a contraindication to resection of colorectal liver metastases. [22][23][24][25] Moreover, a margin of 1 mm seems to be appropriate, despite the fact that the pathological report will define the procedure as a microscopic irradical resection. 24 Current techniques with ultrasonic dissectors aspirate a part of the liver parenchyma interposed between the specimen and the normal liver, making assessment of the true margin difficult.…”
Section: Discussionmentioning
confidence: 99%
“…More wedge resections can be performed because several recent studies have indicated that a margin less than 1 cm is not a contraindication to resection of colorectal liver metastases. [22][23][24][25] Moreover, a margin of 1 mm seems to be appropriate, despite the fact that the pathological report will define the procedure as a microscopic irradical resection. 24 Current techniques with ultrasonic dissectors aspirate a part of the liver parenchyma interposed between the specimen and the normal liver, making assessment of the true margin difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the resection margin in this analysis can be considered controversial, since, in practice, patients with compromised resection margins do not present disease-free intervals (12) . However, the data of studies with strict control of the resection margins show that although such patients have lower rates of disease-free survival, recurrence does not occur more frequently in the resection margin (probable site of residual disease), but in other parts of the liver or other organs (3,18,20) . Regarding the presence of extrahepatic disease at diagnosis, it is understandable that the pattern of dissemination does in fact strongly contribute to the emergence of new foci of disease after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic resection remains a well accepted modality in the treatment of patients with colorectal liver metastases (CRLM) with 5 year overall survival (OS) ranging from 37 % to 58 % [1][2][3][4] and 5 year disease free survival (DFS) ranging from 11 % to 50 % [3,[5][6][7][8][9][10][11][12][13][14]. Recurrence of the disease after resection still remains a challenge and adversely affects the long term outcomes.…”
Section: Introductionmentioning
confidence: 99%